2019
DOI: 10.1128/aem.01007-19
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus in the Chesapeake Bay: OperationalIn SituPrediction and Forecast Models Can Benefit from Inclusion of Lagged Water Quality Measurements

Abstract: Vibrio parahaemolyticus is a leading cause of seafood-borne gastroenteritis. Given its natural presence in brackish waters, there is a need to develop operational forecast models that can sufficiently predict the bacterium’s spatial and temporal variation. This work attempted to develop V. parahaemolyticus prediction models using frequently measured time-indexed and -lagged water quality measures. Models were built using a large data set (n = 1,043) of surface water samples from 2007 to 2010 previously analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Using this approach, we determined that significant predictive variables peak in advance of V. parahaemolyticus potentially contributing to a hysteresis or loading of the systems, setting up conditions that are optimal for V. parahaemolyticus . Davis et al, 2019 [79], recently reported that environmental variables approximately one month proceeding collection were significant to predicting V. parahaemolyticus concentrations in the Chesapeake Bay suggesting they might also be observing this type of lagged effect from a loading of the system. The application of harmonic regression and peak timing here demonstrates how biological complexities and limitations of sampling frequency can be overcome while also providing the resolution to detect temporal patterns between dependent and independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we determined that significant predictive variables peak in advance of V. parahaemolyticus potentially contributing to a hysteresis or loading of the systems, setting up conditions that are optimal for V. parahaemolyticus . Davis et al, 2019 [79], recently reported that environmental variables approximately one month proceeding collection were significant to predicting V. parahaemolyticus concentrations in the Chesapeake Bay suggesting they might also be observing this type of lagged effect from a loading of the system. The application of harmonic regression and peak timing here demonstrates how biological complexities and limitations of sampling frequency can be overcome while also providing the resolution to detect temporal patterns between dependent and independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Beach and water warnings (#11) are advisories and forecasts such as for the presence of HABs and their toxins, sewage pollution, other contaminants, and high concentrations of Vibrio bacteria in recreational waters and drinking water supplies. Multiple modeling tools are available for forecasting HABs and Vibrios and the accuracy and coverage of these systems are increasing rapidly (95)(96)(97)(98). In addition, the US CDC supports the One Health Harmful Algal Bloom System (OHHABS), a voluntary reporting system for states and territories to contribute information on incidences of HABs and associated illnesses in humans and animals (99,100).…”
Section: Resultsmentioning
confidence: 99%
“…Coastal Vibrio spp. abundances correlate to hydrographic factors ( 10 ), such as temperature, e.g., ≥20 ° C ( 11 ), and salinity, e.g., 5–20 ppt and 15–36 ppt for V. vulnificus ( 12 15 ) and V. parahaemolyticus ( 12 , 16 , 17 ), respectively. Estuarine conditions also affect vibrios.…”
Section: Introductionmentioning
confidence: 99%